Integrating water quality model and aeration with IoT technology in water quality management: A conceptual framework - Yahaya, Saifudin Hafiz; Mahdzir, Mira Mazlina; Md Fauadi, Muhammad Hafidz Fazli; Tneh, Tze Yeow (Malque Publishing, 2025)
Eutrophication poses a significant threat to both human population growth and aquatic life. It gives rise to a range of issues, including algae blooms, loss of habitat, reduced self-purification capacity, and changes in the biodiversity system. In order to restore the ecosystem, it is imperative to implement water quality management measures to combat eutrophication. Common methods for mitigating eutrophication include the use of water quality models, aeration, and IoT technology. Water quality model simulations have been demonstrated to accurately predict future water quality. Aeration, on the other hand, increases oxygen concentration in water through dispersion. Furthermore, the utilization of IoT in water quality monitoring provides users with precise and real-time data. Despite research findings that suggest the effectiveness of water quality models, aeration, and IoT technologies in addressing eutrophication, their current integration is inadequate. Therefore, the aim of this paper is to develop a conceptual framework that incorporates water quality models, aeration, and IoT technology to regulate water quality, with a specific focus on preventing the eutrophication issue. The conceptual framework was created by studying existing research on frameworks for water treatment, water quality modelling, aerators, and IoT technologies. Several adjustments were made to tailor the general framework to the specific requirements of this study. The discussion emphasizes the advantages of conceptual framework development in managing water quality, which integrates water quality models, aerators, and IoT technologies. This framework is expected to serve as an effective tool for managing eutrophication in water, while also promoting sustainable measures to address water contamination.